2016
DOI: 10.9799/ksfan.2016.29.6.899
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drink Consumption Status and Associated Factors among Male and Female High School Students in Deajon Area

Abstract: The purpose of this study was to determine factors related to the consumption of energy drinks among male and female high school students in Daejeon. The research data, derived from the self-administered questionnaire method, was collected from 664 students in fifteen high schools during the spring of 2016. A total of 542 complete questionnaires were analyzed (response rate: 79.8%). Approximately 73% of the students self-reported having consumed energy drinks, with a greater percentage of male (as opposed to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Throughout the study, it was found that because of less education, the majority of participants assume that energy drinks is healthy for children, teenagers and adults. By intake of energy beverages [39].…”
Section: Municipalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the study, it was found that because of less education, the majority of participants assume that energy drinks is healthy for children, teenagers and adults. By intake of energy beverages [39].…”
Section: Municipalitymentioning
confidence: 99%
“…A study by Ryu SH [39], investigated the energy consumption status and related factors among male and female high school students in the Deajon area study. To test energy consumption in Daejeon high school students Sample size of 664 high school students was picked at fifteen.…”
Section: Municipalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents who consume HCBs may be at higher risk of caffeine intoxication than adults [ 9 ]. Korean adolescents may be particularly vulnerable to HCB abuse and caffeine intoxication, as many rely on HCBs to stay awake or focus on studying [ 10 ]. The Korean government attempted to limit adolescents’ caffeine intake by restricting advertisements, requiring warning labels, and banning the sale of HCBs on school grounds [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Korean adolescents may be particularly vulnerable to HCB abuse and caffeine intoxication, as many rely on HCBs to stay awake or focus on studying [15,16]. As such, the Korean government attempted to limit adolescent's caffeine intake by (i) requiring warning labels, (ii) restricting advertisement, and (iii) banning the sale of HCBs on school grounds [9,10,[17][18][19].…”
mentioning
confidence: 99%